Sleep disorders and starting time to school impair balance in 5-year-old children Distúrbios do sono, período escolar e equilíbrio em crianças com 5 anos de idade - Cristiane Aparecida Moran; Luciane B.C. Carvalho; Lucila B.F. Prado; Gilmar F. Prado (Arquivos de Neuro-Psiquiatria)
OBJECTIVE: To verify if sleep disorders and differents starting time to school have impaired motor skills in 5-year-old children. METHOD: Cross-sectional design consisting of 132 children with sleep disorders and 136 normal controls of the public school in the city of São Paulo. The group with sleep disorders was identified based on a questionnaire, and motor tests for global motor coordination, fine motor coordination, perceptual-motor coordination, and static and dynamic balance were applied in all children. RESULTS: In the static balance test, more specifically in the sharpened Romberg (Tandem) test, 34% of boys from the study group, who studied in the morning, failed the test (p < 0.05). In the single leg stance test, 62% of boys from the study group who studied in the morning failed (p< 0.05). CONCLUSION: This study suggests that sleep disorders may interact with the school period and alter motor performance, especially in boys studying in the morning. OBJETIVO: Verificar se distúrbios do sono e diferentes períodos escolares comprometem as habilidades motoras de crianças de 5 anos. MÉTODO: Realizou-se estudo transversal com 132 crianças com distúrbio do sono e 136 controles normais de escolas públicas da cidade de São Paulo. Foram utilizados questionários para distúrbios do sono e testes para coordenação motora global, motora fina, percepto-motora, equilíbrio estático e dinâmico. RESULTADOS: No teste de equilíbrio estático, mais especificamente na prova pé ante pé, 34% dos meninos do grupo estudo, que estudavam no período da manhã, falharam no teste (p < 0,05). Na prova de apoio monopodal, 62% dos meninos do grupo estudo, que estudavam no período da manhã, falharam no teste (p < 0,05). CONCLUSÃO: Este estudo sugere que os distúrbios do sono podem interagir com o período escolar e alterar a performance motora, principalmente de meninos que estudam no período da manhã.